Ruling on Dealing with Spoiled Foods in Islamic Fiqh - Kamal Sadiq Yasin; Aveen Mohamed Shareef (Zanco Journal of Humanity Sciences)
This research deals with the statement of the legal ruling on how to deal with spoiled foods and foods that cause harm between human health and the environment, and these foods are not suitable for human consumption and some are not even suitable for animals, and the research deals with an issue that affects the daily life of ordinary people necessary related to eating and drinking. In Sharia It is forbidden for a person to eat what is harmful and not beneficial to him. It is obligatory for Muslim to protect himself from disease, destruction and death.